Epidemiology of subclinicul mastitis and their antibacterial susceptibility in smallholder dairy farms, Chiang Mai Province, Thailand - Witaya Suriyasathaporn (2018)
The objectives of this study were to identify the bacteria causing subchmcal mastitis at the beginning of the rainy season to define the factors associated with subclinical mastitis caused by various pathogens and to identify antibiotic susceptibility and resistance. About 42 farms from the Mae-On Dairy Cooperative participating in the Herd Health Management Program (HHPM), Faculty of Veterinary Medicine, Chiang Mai University were included in the study. The study was conducted in June, 2008. From the protocol of HHPM, all farms had to collect a milk sample from each milking cow for measurement of Somatic Cell Counts (SCC) once a month. At the cut-off point of SCC = 200,000 cells mL-1 the cows were deemed to haveintramammary infection. Cows in 3 groups were checked for subclinical mastitis in quarter levels using the California mastitis test within 2 weeks after SCC measurement. A cow with CMT score ≥+l for at least one quarter was identified as a subclinical mastitis cow and was included into the study. Milk samples from subclinical mastitis quarters were collected with aseptic techniques. The fisher exact χ2-tests were used to evaluate the association of pathogens with antibiotic resistant and the associated factors. The significant levels were defined at p<0.05. In total, 133 quarters from 68 cows and 22 dairy farms were included in the study. C. bovis (28%) and Coagulase Negative Staphylococci (CNS) (28%) were the main bacteria isolated in this study. Stap. aureus (8%) and St. agalactiae (2%) as contagious pathogens were at low levels. An occurrence of subclinical mastitis from S. aureus was significantly associated with subclinical mastitis status in which most S. aureus subclinical mastitis showed chronic status of subclinical mastitis. Most subclinical cases occurred during late lactation (54%). Occurrences of subclinical mastitis from Stap. aureus and C. bovis were associated with period of lactation (p<0.05). About 99 bacterial identifications were used for antibiotic susceptibility test. Bacteria that were significantly associated with resistant patterns were St. uberis, S. aureus and S. dysgalactaie. Subclinical mastitis with St. uberis was resistant to most antibiotics (p<0.05); subclinical mastitis with Stap. aureus and CNS wassusceptible for most antibiotics. © Medwell Journals, 2011.